Applications of the Fractional Calculus: On a Discretization of Fractional Diffusion Equation in One Dimension - Kisela, Tomas (Communications - Scientific Letters of the University of Zilina, 2010)
The paper discusses the problem of classical and fractional diffusion models. It is known that the classical model fails in heterogeneous structures with locations where particles move at a large speed over a long distance. If we replace the second derivative in the space variable in the classical diffusion equation by a fractional derivative of order less than two, we obtain the fractional diffusion equation (FDE) which is more useful in this case. In this paper we introduce a discretization of FDE based on the theory of the difference fractional calculus and we sketch a basic numerical scheme of its solution. Finally, we present some examples comparing classical and fractional diffusion models.
Keywords: no keywords